Unusual song of an individual Cyprus Scops Owl Otus cyprius (Aves: Strigidae). Issue 4 (2nd October 2017) - Flint, Peter
Abstract : Cyprus Scops Owl, Otus cyprius, has recently been split from Eurasian Scops Owl, Otus scops, partly because of song differences. Spectrographic analysis of a more recent O. cyprius song recording shows that it differs from that of O. scops in phrase length and frequency more than previously analysed recordings. The recorded song is also most unusual in possessing two phrases each containing 11 consecutive quiet notes; these two phrases are also remarkably similar in pattern, timing and amplitude. Previously only three consecutive quiet notes were known from O. cyprius though so far its multiple quiet note phrases have been little studied.